Silence, Rebellion, and Acting-Out of a Silenced Past: Understanding the French Riots From a Postcolonial and Transcultural Perspective - Mansouri, Malika; Feldman, Marion; Lachal, Jonathan; Dozio, Elisabetta; El Husseini, Mayssa’; Moro, Marie Rose (Frontiers in Psychiatry, 2019)
Context and Objectives: According to a sociological study, the adolescents involved in the “suburban riots” of November 2005 were French nationals with a foreign background, including 55% of North African descent. Numerous attempts to interpret the “riots” have been made, but none of them has discussed the impact of the “silenced” colonial history on their filiation. For this reason, the present research set out to overcome this shortfall. Methods: Using a complementarist, transcultural, qualitative research methodology, 15 interviews with French adolescents of Algerian descent were analysed. Results, Analysis and Discussion: The analysis of these interviews highlighted the impact of the past violence in France’s colonial history on family dynamics and intergenerational relationships, which seemed to play a crucial role in the unconscious component of transmission within these families. This discovery led us to a new understanding of the 2005 revolt, envisaging it as a symptom of a disorder situated on several levels: on the level of subjectivity, of trans-generational relationships, and also on the level of social cohesion within French society. The interviews showed how the young interviewees related their current anger to French colonial and post-colonial history. Conclusions: These observations led to a new understanding of the “riots” as a form of acting-out of anger linked to contemporary and past experiences of domination and exclusion.